Quality of life in patients with mild plaque psoriasis - Xiaoyu QIU; Bin YANG; Xiaohua WANG; Peizhen ZHAO; Mudiao CHEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
Objective To investigate the influence of mild psoriasis on the quality of patients' lives. Methods Based on PASI score and quality of life index, a questionnaire was designed to investigate the quality of lives in aspects of physiology, psychology, daily life, social entertainment, family, work and study in 95 patients with mild plaque psoriasis, aged 18~65 years. Logistic regression was used to analyze the quality of life-related factors. Results The quality of lives of 45 patients (47.37%) was affected by psoriasis. Moreover, an increase in one PASI score increased the risk of affecting quality of lives to 1.291 times, while an increase in one PGA score increased the risk of affecting quality of lives to 3.574 times. Conclusion Mild plaque psoriasis can affect the quality of patients' lives to some extent.